Cross Inhibition of MPK10 and WRKY10 Participating in the Growth of Endosperm in Arabidopsis thaliana - Xi, Xiaoyuan; Hu, Zhengdao; Nie, Xuerui; Meng, Mingming; Xu, Hao; Li, Jing (Frontiers in Plant Science, 2021)
The double fertilization product, seeds contain three components: triploid endosperm, diploid embryo, and maternal seed coat. Amongst them, the endosperm plays a crucial role in coordinating seed growth. In Arabidopsis thaliana, the endosperm development was found to be regulated by HAIKU (IKU) pathway and epigenetic regulations. MAPK (MITOGEN-ACTIVATED PROTEIN KINASE) cascades are conserved in eukaryotes and involved in diverse aspects of plant development. However, we know little about MAPK cascades in endosperm development. Here, we report MPK10 has a reverse gradient expression pattern compared to that of WRKY10 in the endosperm. MPK10 interacts with WRKY10 and has an impressive effect on regulating the transcriptional activity of WRKY10. In turn, WRKY10 could inhibit the expression of MPK10 in the early stages of endosperm development. And opposite to iku mutants, the mpk10 mutant produces big seeds. Our data showed MPK10 plays a role in endosperm development with a mutual suppress model between WRKY10 and MPK10.